1981
DOI: 10.1021/ja00399a002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanics calculations and experimental studies of conformations of .delta.-valerolactone

Abstract: The microwave spectrum of the title compound has been determined in the gas phase at room temperature, and the Raman spectrum has been determined on the liquid at room temperature and on the solid at 73 K. From the experimental data it is concluded that there are two conformers separated in energy by approximately 0.6 kcal/mol, and only the more stable one persists in the crystal. The more stable conformer has a very small (<0.1 D) µ<. component of the dipole moment, while this component is much greater for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 5 publications
(10 reference statements)
5
15
0
Order By: Relevance
“…Moreover, the intensity of the band at 831 cm -1 shows that the contribution of boat conformation is bigger than that calculated for the gas phase. The analogous experimental data were obtained by Philip et al 18 for the related molecule, i.e., δ-valerolactone. In that work, a pair of Raman bands at 748 and 798 cm -1 were found and assigned as the ring-breathing vibrations of the half-chair and boat conformations, respectively.…”
Section: Comparison Of Experimental and Theoretical Raman And Roa Spesupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the intensity of the band at 831 cm -1 shows that the contribution of boat conformation is bigger than that calculated for the gas phase. The analogous experimental data were obtained by Philip et al 18 for the related molecule, i.e., δ-valerolactone. In that work, a pair of Raman bands at 748 and 798 cm -1 were found and assigned as the ring-breathing vibrations of the half-chair and boat conformations, respectively.…”
Section: Comparison Of Experimental and Theoretical Raman And Roa Spesupporting
confidence: 78%
“…Most of the literature is devoted to the analysis of the conformations of unsubstituted δ-lactones, i.e., δ-valerolactone. Its conformation was explored both experimentally by 1 H NMR, 13 C NMR, 40,41 and Raman spectroscopy, 18 and theoretically by MM2, 18,42,43 MM3, 43,44 HF/6-31G*, 41,45,46 MP2 or G3 MP2, 45,[47][48][49] and B3LYP methods with different basis sets. [49][50][51][52] All of these calculated data match the experimental one very well, and show that δ-valerolactone exists in halfchair and a little less stable as boat conformations.…”
Section: Results and Discussion Conformational Space Of (à)-R-mevalonmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Molecular mechanics calculations indicated that these two forms corresponded to the two minimum-energy conformations, with the H conformer being the more stable. 22 The 1 H NMR spectrum of 9 showed large values for J 2,3ax (11.0 Hz), J 4ax,5 (11.4 Hz), and especially for J 3ax,4ax (13.0 Hz) thus suggesting a strong preference of the lactone ring for the 4 H 3 conformer. In this conformation the bulky substituents at C-2 and C-5 are equatorially (or quasiequatorially) oriented.…”
Section: Resultsmentioning
confidence: 91%
“…MM calculations were performed using the force field method developed by Allinger and co-workers [32][33][34][35]. The PC-MODEL software [36] was employed to carry out the calculations.…”
Section: Simulation Methodology and Computational Detailsmentioning
confidence: 99%